Best practices to maximise adaptation strategies to the local markets at a multinational company: the case of Kimberly Clark - Biz Lage, Wendy Melanie (2024)
Fil: Biz Lage, Wendy Melanie. Universidad de San Andrés. Escuela de Negocios; Argentina.